Antimicrobial activity of coffee-based solutions and their effects on Streptococcus mutans adherence - Eloiza Helena da Silva Brandão; Luciane Dias Oliveira; Luís Fernando Landucci; Cristiane Yumi Koga-Ito; Antonio Olavo Cardoso Jorge (Brazilian Journal of Oral Sciences, 2016)
The aim of this study was to evaluate the antimicrobial activity of different coffee solutions and their effects on the adherence of Streptococcus mutans to glass surface. Coffee solutions were prepared with three commercial products (Pilão, Mellita and Café do Ponto) by two different methods (simple and boiled) (n=15). A control group was also included in the study. For antimicrobial activity testing, tubes containing coffee solution and culture medium were inoculated with a suspension of S. mutans ATCC 35688 and incubated for 1min, 1h, 2h and 4h. Serial dilutions and plating on BHI agar were performed. S. mutans adherence to glass in presence of the different coffee solutions was also tested. The number of adhered bacteria (CFU/mL) was determined by plating method. The results were statistically analyzed by ANOVA and Tukey’s test. The tested coffee solutions did not reduce the number of colony forming units of S. mutans in relation to the control at all evaluation periods. All the solutions reduced significantly the adherence of S. mutans to the glass surface in relation to control. The tested coffee solutions did not present any antimicrobial effect on Streptococcus mutans, however, all the coffee solutions reduced significantly the adherence of S. mutans to the glass surface.